Pak Din Teega / Fakhrul Izzuddin Mahidin - Mahidin, Fakhrul Izzuddin (2021)
Pak Din Teega is a small company founded by Fakhrul Izzuddin Bin Mahidin, student of UiTM Puncak Alam. Even that, all the products are not produced by himself. He acts as dropship/agent for Teega Food, which the producer for all product on Pak Din Teega. He manages the business by himself alone including packaging for delivery, marketing, and promotion. Pak Din Teega operates through online only due to lack of budget and Covid-19 crisis. Currently, business based on online platform are more relevant and effective because of restriction to travel and movement across the city due to Covid-19 crisis. Mr. Fakhrul manages the business from home based on Facebook platform. He used Facebook as platform to run his business because it is do not charge even a cent to market any business, able to share picture and video especially for long duration video and help to market the products to people nearby and page’s follower. For the delivery of goods, he uses courier service like JnT Express and PosLaju to deliver across all states in Malaysia, which cost RM 8 - RM 12. Beside that, he also provides cash on delivery (COD) services for customers located around the district of Kuala Selangor with charged RM 5 - RM 8, based on COD location. Pak Din Teega only selling 2 type of products which named Mama Teega Crispy Snack and Baby Teega Crispy Snack. The ingredients for those products are same, the different of them are on the size and packaging only. The ingredients are corn flour, premium cheese, chili, and sugar, the producer does not used artificial coloring and artificial flavoring to make a healthier snack. The products should be healthier because the target market for Pak Din Teega is kid until elders. Nowadays, parents are more aware about the food eaten by their kids, they always want their kids eat something good for health, that why the producer produce that product because there a demand on healthier snack for kids.